2021
DOI: 10.3389/fonc.2021.622263
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Overexpressed Tumor Suppressor Exosomal miR-15a-5p in Cancer Cells Inhibits PD1 Expression in CD8+T Cells and Suppresses the Hepatocellular Carcinoma Progression

Abstract: BackgroundHepatocellular carcinoma (HCC) is the most common primary liver tumor, and the main reason is the unclear pathogenesis of HCC, which leads to a high fatality rate of HCC. Therefore, it is of great clinical significance to explore the molecular mechanism of HCC and find a targeted therapeutic approach from the molecular level.Materials and MethodsMicroRNA-15a-5p (miR-15a-5p) expression level was measured by bioinformatics and qRT-PCR. Luciferase assay and RIP assays were used to verify the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Disposing of tumour suppressors could bring a growth advantage to PCa cells [71]. In support of this, Zhang et al observed this kind of a difference in the tumour suppressor miR-15a-5p levels of hepatocellular carcinoma EV and cells [72]. Additionally, in the case of mRNAs, the transcripts in parental cells and their EV may differ [73].…”
Section: Discussionmentioning
confidence: 87%
“…Disposing of tumour suppressors could bring a growth advantage to PCa cells [71]. In support of this, Zhang et al observed this kind of a difference in the tumour suppressor miR-15a-5p levels of hepatocellular carcinoma EV and cells [72]. Additionally, in the case of mRNAs, the transcripts in parental cells and their EV may differ [73].…”
Section: Discussionmentioning
confidence: 87%
“…34 Moreover, it also inhibited the function of NK cells by increasing TIM-3 expression levels through the degradation of miR-449c-5p, thus resulting in resistance to anti-PD-1 therapy. 34,35 Therefore, reducing the expression levels of circUHRF1 through the exosomal circUHRF1/miR-449c-5p/TIM-3 pathway improves the efficacy of anti-PD-1 therapy, which might provide a promising method for HCC immunotherapy. T-cell immunoglobulin and immunoreceptor tyrosine-based inhibitory motif (ITIM) domain (TIGIT) are expressed on NK cells, regulatory CD4 + T cells, and effector T cells.…”
Section: The Regulatory Signals Of Pd-1 In Hccmentioning
confidence: 99%
“…CircUHRF1 inhibited the secretion of natural killer (NK) cell‐derived TNF‐α and IFN‐γ 34 . Moreover, it also inhibited the function of NK cells by increasing TIM‐3 expression levels through the degradation of miR‐449c‐5p, thus resulting in resistance to anti‐PD‐1 therapy 34,35 . Therefore, reducing the expression levels of circUHRF1 through the exosomal circUHRF1/miR‐449c‐5p/TIM‐3 pathway improves the efficacy of anti‐PD‐1 therapy, which might provide a promising method for HCC immunotherapy.…”
Section: The Regulatory Signals Of Icp In the Development Of Hccmentioning
confidence: 99%
“…Tumor-cell-derived exosomes can be directly transported into CD8+ T cells, tumor-infiltrating T cells, or regulatory T cells to inhibit their anti-tumor function or modulate their cellular behaviors [ 30 , 31 , 32 , 33 ]. Furthermore, HCC-derived exosomes can induce nature killer (NK) cell activation, attenuate NK cell cytotoxicity, and arrest them to secret cytokines [ 34 , 35 , 36 ].…”
Section: Influence Of Exosomes On Tumor Microenvironment Of Hccmentioning
confidence: 99%